Upholding the Strategy on Hiring Employee under Meritocracy Procedure towards a Refined Performance (International Journal of Scientific Research and Management (IJSRM), 2024)
In today’s competitive business environment, companies are constantly searching for novel recruitment and retention strategies. Recruitment and selection of employees are essential components of this process due to their direct impact on a company’s overall performance and growth. Numerous companies have instituted a meritocracy system to ensure that the hiring process is equitable, efficient, and in line with company objectives. A meritocracy is a system that emphasizes the significance of individual merit and performance in determining whether or not someone is hired or promoted. It promotes the notion that rewards should be distributed based on a person’s abilities, skills, and achievements, as opposed to bias, partiality, or personal relationships. By enforcing a meritocracy method and fostering a culture of justice, openness, and equal opportunity, organizations strive to create a level playing field for all applicants. In government agencies, unfair employment practices pose a serious problem. Consequently, the researchers propose to contribute to this issue by preserving the meritocracy recruiting method, which addresses a variety of issues such as employee comprehension of meritocracy and its consequences. The significance of enhanced performance and the enormous difference it can produce if not executed properly. A meritocracy method is one in which candidates are recruited, chosen, employed, and promoted solely based on their merit. This incorporates suitability for work and merit, with the aim of eradicating unethical employment practices and fostering effective job performance that contributes to the development of one’s own community. The study investigates the importance of maintaining the practice of selecting personnel on the basis of merit. It will examine the many facets of this strategy, including its benefits, drawbacks, and prospective effects on organizational performance.